The Eradication of Women and Children Trafficking in Jember Regency in Relations to the Legal Protection for Victims in the Health Perspective (Medico Legal Update, 2020)
The development of human trafficking has changed to happen to the kinds of people who are disadvantaged,such as woman and children. The trafficking of woman and children is one of the bad forms treatment fromthe exploitation activity which is faced by woman and children. Trafficking is included as a crime and ahuman rights violation. Indonesia itself is a region where woman and children trafficking happens, either ascountry of the victims’ origin or as a transit country. Some regions in Indonesia are estimated as targets ofborder countries’ crime syndicate activities which organize woman and children trafficking. This researchanalyzes the women and children trafficking in Jember Regency in the perspectives of law and health.